PENERAPAN QUANTUM TEACHING UNTUK MENGURANGI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL POKOK BAHASAN ARITMETIKA SOSIAL DI KELAS VII SMP NEGERI 7 JEMBER SEMESTER GASAL TAHUNAJARAN 2013/2014 - Husna, Elok Asmaul; Dafik, D; Hobri, H (KadikmA, 2014)
Abstract.This study aimed to know the application of quantum teaching in improving studentâs mistakes for social arithmetic topic at seventh grade of juniorhigh school. This study involved grade VIID of SMPN 7 Jember school year 2013/2014 . The research method is a classroom action research. There are four type of studentâs mistake, namely the error of using a data, the error of theorem and definition application, technical error, inference error. The result shows that the total error at cycle I reach 38,21% and cycle II reach 28,45%. While the studentâs activity of cycle I is 88,86% and cycle II 93,90%. It can be concluded that the quantum teaching model can reduce the students mistakes. Key Words:quantum teaching, social arithmetic, studentâs activity, studentâs mistakes